2018
DOI: 10.1097/md.0000000000010357
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of cystatin A expression in progression of esophageal squamous cell carcinoma

Abstract: We previously conducted transcriptome analysis of a paired specimen of normal and esophageal squamous cell carcinoma (ESCC) tissues and found that mRNA expression of cystatin A (CSTA), a member of the cystatin superfamily, was perturbed in tumors compared with that in the background mucosa. However, little is known about the significance of CSTA expression in ESCC.The mRNA expression of CSTA was evaluated by qRT-PCR using 28 paired frozen samples of tumor and nontumor mucosae. The protein expression of CSTA wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…We found a significant downregulation of IL-23 to be associated with BM; however, it is possible that similar to the results found by Shiba et al, 13 mRNA expression could be significantly decreased overall but still have areas within the tumor showing increased expression. Again, this suggests that further studies investigating the immunostaining of tumor samples may be beneficial.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We found a significant downregulation of IL-23 to be associated with BM; however, it is possible that similar to the results found by Shiba et al, 13 mRNA expression could be significantly decreased overall but still have areas within the tumor showing increased expression. Again, this suggests that further studies investigating the immunostaining of tumor samples may be beneficial.…”
Section: Discussionsupporting
confidence: 85%
“…11 Studies have also indicated that CSTA suppressed ultraviolet-induced apoptosis in keratinocytes by the inhibition of caspase 3. 12 A recent study in 2018 by Shiba et al 13 showed that the mRNA expression of CSTA was significantly decreased in esophageal squamous cell carcinoma with a P <0.001; however, some portions of the tumor tissues showed high CSTA expression levels, and these areas showed the most advanced tumor invasion. The authors felt that although a significant portion of cells in the tumor were attempting to downregulate CSTA, the cells unable to do so had advanced tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal carcinoma (EC) is a common malignant gastrointestinal tumor and one of the main reasons for tumor-related death. 1 It has been estimated that in 2012, 455,800 patients were newly diagnosed with EC and 400,200 EC-related deaths occurred globally. 2 Smoking, drinking, and high body mass index are the risk factors for EC, and it has been validated that the ingestion of vegetables and fruits can reduce the morbidity of EC.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CSTs may also be associated with tumor progression. Notably, CSTs have been reported to be associated with the progression of various types of cancer, including bladder cancer (40), breast cancer (41,42), esophageal cancer (43), ovarian cancer (44) and prostate cancer (45). The results of GSEA in the present study indicated that CST7 was significantly enriched in liver cancer progression.…”
Section: Discussionmentioning
confidence: 99%